Μ-Pseudo almost periodic solutions for delayed partial functional differential equations in admissible spaces. Issue 4 (12th March 2021) - Jendoubi, Chiraz
Abstract : We present a theory of existence and uniqueness of μ -pseudo almost periodic solution for a delayed non-autonomous partial functional differential equation in the exponential dichotomic case, where the nonlinear operator F satisfies the ϕ -Lipschitz condition and ϕ belongs to some admissible spaces. Moreover, we prove the existence of an invariant stable manifold around the μ -pseudo almost periodic solution in that case. We give finally an application to illusrate our results.